Assessing common defect on commercial complexes in Shah Alam / Noor Hafizah Adnan - Adnan, Noor Hafizah (Faculty of Architecture, Planning and Surveying, 2015)
Malaysia is one of the developing countries and many projects are being implemented. The construction industry helps to generate the nation’s economy as well as providing benefits to construction companies. But some of these firms acted unprofessionally by involving in projects that do not meet the standard especially in commercial complexes. In commercial complexes, the common phenomena are defect and failures. The defects commonly include any deficiency which furnishing or performing of the construction and observation, inspections, supervisions, planning and designing. Defects occurring in various forms and different extents in all types of buildings, irrespective of age. The agents that affected the commercial complexes defect occurs is variation, locations, construction work, the use and condition of the affected buildings. The approach to prevent the defect occurred in commercial complexes should be taken by building management team or others involved parties. In order to achieve the aim, this dissertation will identify the common defects found in commercial complexes and highlight the agents that influences the defects occurred. Apart of that, it will also recommend the approach that should be taken to prevent the defect occurs. The study area is located at 3 commercial complexes in Shah Alam which is PAS complex, PKNS complex and SACC mall. The methodology adopted is through literature review, questionnaire with the building management team and site observation. A comprehensive literature research, which is related to this dissertation, was carried out based on the analyses of related books, journals, newspapers and magazine. Data was then analysed using statistical methods. The data analysed determined that most of the common building defect occurred in commercial complexes at Shah Alam is PKNS complex. There no major of common building defects occur to the commercial complexes of PAS mall and SACC mall. In addition, majority of the building management team has had knowledge and agreed about the agent's influences information related to the building defects occurred in commercial complexes and have been strongly agree and agree with all of approach of defect preventives. The common approach of defect prevention can improve the both of quality and productivity for commercial complexes. The knowledge and finding gained in this study can be used for future references.